2020
DOI: 10.1080/2162402x.2020.1758606
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 suppresses the therapeutic activity of cancer vaccines through the inhibition of CD8 + T-cell responses

Abstract: Antitumor immunity is mediated by Th1 CD4 + and CD8 + T lymphocytes, which induce tumor-specific cytolysis, whereas Th17 CD4 + T cells have been described to promote tumor growth. Here, we explored the influence of IL-17 on the ability of therapeutic vaccines to induce the rejection of tumors in mice using several adjuvants known to elicit either Th1 or Th17-type immunity. Immunization of mice with Th1-adjuvanted vaccine induced high levels of IFN-γ-producing T cells, whereas injection with Th17promoting adjuv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In terms of functional consequences, we can hypothesize from previous works that GILZ downregulation in mig/resDC2 would favor Th17 CD4 T-cell priming while its increase in resDC1 would rather promote Treg expansion [20,21,24,29]. Together, this would compromise anti-tumor response efficiency [51,52]. The opposite regulation of GILZ in cDC1 and cDC2 from tumorbearing mice is of particular interest in view of its contribution in the control of anti-cancer therapy efficiency [23].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of functional consequences, we can hypothesize from previous works that GILZ downregulation in mig/resDC2 would favor Th17 CD4 T-cell priming while its increase in resDC1 would rather promote Treg expansion [20,21,24,29]. Together, this would compromise anti-tumor response efficiency [51,52]. The opposite regulation of GILZ in cDC1 and cDC2 from tumorbearing mice is of particular interest in view of its contribution in the control of anti-cancer therapy efficiency [23].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these data provide supporting evidence that IL-17 may play a dual role in human tumor immunity. Moreover, the activation of tumor-specific Th17 cells may promote the therapeutic efficacy of cancer vaccines ( 40 ). In our study, we found that CTL responses induced by the Th1/Th17 cellular response ( Figure 4 ) were also dependent on IFN-γ, and type I IFN signaling by CD8 + T cell responses induced by OVA/SND were stronger for IFN-γ and IL-17 than those induced in the other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we suggest that the hub FRGs have the potential to be involved in CD4 + T cell activation, especially Th cells. The activated Th cells may promote antitumor immunity in GC ( Dadaglio et al, 2020 ). PSAT1 (phospholipid sterol acyltransferase 1) has been reported to be critically important for the transition from p-Pyr to p-Ser ( Mullarky et al, 2016 ) and further affects ferroptosis ( Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%